The Delegation of the Application and Revision of Taxes Ceded to the Autonomous Communities: Assessment and Perspectives - Eva María Cordero González (Revista d'Estudis Autonòmics i Federals, 2023)
The paper deals with several current issues related to the transfer to the autonomous regions of the competences for the application of fully assigned taxes. It deals, in particular, with the problem of the regulatory powers of the autonomous regions in relation to tax procedures, following Ruling 65/2020 of the Constitutional Court, of 18 June 2020. Likewise, we analyse the implications that the introduction of the reference value as a taxable base for ISD and ITPAJD has on the distribution of delegated powers between the State and the autonomous regions, considering it necessary to reform Law 22/2009, particularly with regard to the revision. Finally, we refer to some of the recommendations contained in the reports of the General Inspectorate of the Ministry of Finance on the exercise of delegated powers incorporated annually in the State Budget. These reports state very relevant differences in the means and way of acting of the different autonomous community administrations in the application of the assigned taxes, considering it necessary to move towards an integrated tax administration.